System of Recruitment of Legal Profession in a Nation of Law of Pancasila - Anam, Saiful (The Indonesian Journal of International Clinical Legal Education, 2019)
The regulation of system and mechanism of recruitment of legalprofession like Advocate/ Lawyer and Notary Public still has a numberof weaknesses, and it also still raises some issues in Indonesia. There arestill problems in the recruitment of advocates, for example, we find thatthere are multiple mechanisms used by advocate organizations. Someadvocate organizations still implement the professional education ofadvocacy as the requirement for the candidates to get the exam, andthere are also some advocate organizations that require the candidatesto take the exam before getting the professional education. Someproblems do also exist in the profession of notary public, in which thecandidates should obtain Master of Public Notary. On the other side,some professional education could be implemented by non degreesystem, however, most of the professional educations are implementedthrough advanced educational systems. For example, when thecandidates of notary public completed the notary school, then they willbe awarded Master of Public Notary. The researcher used normativeand sociological legal research method, and therefore, this researchwould generate the recruitment system of legal profession that is inaccordance with the values and principles in the Pancasila-basedNation of Law.